2016
DOI: 10.1017/jns.2016.29
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a web-based food record tool and a food-frequency questionnaire and objective validation using the doubly labelled water technique in a Swedish middle-aged population

Abstract: Two web-based dietary assessment tools have been developed for use in large-scale studies: the Riksmaten method (4-d food record) and MiniMeal-Q (food-frequency method). The aim of the present study was to examine the ability of these methods to capture energy intake against objectively measured total energy expenditure (TEE) with the doubly labelled water technique (TEEDLW), and to compare reported energy and macronutrient intake. This study was conducted within the pilot study of the Swedish CArdioPulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 44 publications
6
46
1
4
Order By: Relevance
“…To date, however, the evidence for the accuracy of food records against recovery biomarkers has been limited to energy. Studies found that energy intake on multiple-day food records, on average, was underestimated by 20-25% compared with DLW (37)(38)(39)(40). More recently, the Nutrition and Physical Activity Assessment Study (NPAAS) evaluated a 4DFR against recovery biomarkers in women and found that mean energy intakes were underestimated by 20%, whereas absolute intakes of protein and sodium were underestimated by 2-4% and the absolute intake of potassium was overestimated by 20% (7,11).…”
Section: Resultsmentioning
confidence: 99%
“…To date, however, the evidence for the accuracy of food records against recovery biomarkers has been limited to energy. Studies found that energy intake on multiple-day food records, on average, was underestimated by 20-25% compared with DLW (37)(38)(39)(40). More recently, the Nutrition and Physical Activity Assessment Study (NPAAS) evaluated a 4DFR against recovery biomarkers in women and found that mean energy intakes were underestimated by 20%, whereas absolute intakes of protein and sodium were underestimated by 2-4% and the absolute intake of potassium was overestimated by 20% (7,11).…”
Section: Resultsmentioning
confidence: 99%
“…Strengths of the present study were the nation-wide, population-based approach employed for participant recruitment and the fact that dietary intake was assessed by repeated recordings, rather than a food frequency questionnaire, and covered several consecutive days, allowing variations in more frequent nutrients in the overall diet to be captured [14]. Still, all methods for recording diet intake suffer from recall bias, with systematic under-reporting being most common and most serious for data inference [28]. To limit the effects of under-reporting, we excluded subjects with the lowest energy intake and those who reported unrealistic energy intake relative to estimated need [18], and we energystandardized all dietary measures by the residual method [29].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was to use carotenoids as biomarkers of fruit and vegetable intake and alkylresorcinols as biomarkers of whole grain wheat and rye intake, when examining and comparing the ability of the two self-reported methods to capture habitual dietary intake. The validation on energy intake has previously been carried out [29]. Both methods are web-based and the validation process involves novel biomarkers, which makes this topic of interest for anyone involved in developing and evaluating new dietary assessment methods.…”
Section: Introductionmentioning
confidence: 99%